Deep learning of model- and reanalysis-based precipitation and pressure mismatches over Europe - Patakchi Yousefi, Kaveh; Kollet, Stefan (Frontiers in Water, 2023)
Physically-based numerical weather prediction and climate models provide useful information for a large number of end users, such as flood forecasters, water resources managers and farmers. However, due to model uncertainties arising from e.g., initial value and model errors, the simulation results do not match the in-situ or remotely sensed observations to an arbitrary accuracy. Merging model-based data with observations yields promising results benefiting simultaneously from the information content of the model results and observations. Machine Learning (ML) and/or Deep Learning (DL) methods have shown to be useful tools in closing the gap between models and observations due to the capacity in the representation of the non-linear space-time correlation structure. This study focused on using UNet encoder-decoder Convolutional Neural Networks (CNN) for extracting spatiotemporal features from model simulations for predicting the actual mismatches (errors) between the simulation results and a reference data set. Here, the climate simulations over Europe from Terrestrial Systems Modeling Platform (TSMP) were used as input to the CNN. The COSMO-REA6 reanalysis data was used as reference. The proposed merging framework was applied to mismatches in precipitation and surface pressure representing more and less chaotic variables, respectively. The merged data show a strong average improvement in mean error (~ 47%), correlation coefficient (~ 37%), and root mean square error (~ 22%). To highlight the performance of DL-based method, the results were compared with results obtained by a baseline method, quantile mapping. The proposed DL-based merging methodology can be used either during the simulation to correct model forecast output online, or in a post-processing step, for downstream impact applications such as flood forecasting, water resources management, and agriculture.